Bio-fabrication of Zinc Oxide nanoparticles to rescue Mung Bean against Cercospora leaf spot disease - Rafiq, Hamza; Aftab, Zill-e-Huma; Anjum, Tehmina; Ali, Basharat; Akram, Waheed; Bashir, Uzma; Mirza, Faisal Shafiq; Aftab, Muzammil; Ali, Muhammad Danish; Li, Guihua (Frontiers in Plant Science, 2022)
Plant disease management using nanotechnology is evolving continuously across the world. The purpose of this study was to determine the effect of different concentrations of green synthesized zinc oxide nanoparticles (ZnO NPs) using Trachyspermum ammi seed extract on Cercospora leaf spot disease in mung bean plants under in-vitro and in-planta conditions. Additionally, the effects on mung bean agronomic and physiological parameters were also assessed. The green synthesized ZnO NPs were characterized using UV-visible spectroscopy, Fourier-transform infrared spectroscopy (FTIR), X-ray diffraction (XRD) and Scanning electron microscopy (SEM). Green synthesized NPs were tested for their ability to inhibit fungal growth at five different concentrations under in-vitro experiment. After 7 days of inoculation, ZnO NPs (1200 ppm) inhibited mycelial growth substantially (89.86% ± 0.70). The in-planta experiment showed statistically significant result of disease control (30% ± 11.54) in response to 1200 ppm ZnO NPs. The same treatment showed statistically significant improvements in shoot length, root length, number of leaves, number of pods, shoot fresh weight (28.62 %), shoot dry weight (85.18 %), root fresh weight (38.88 %), and root dry weight (38.88 %) compared to the control. Our findings show that green synthesized ZnO NPs can control Cercospora canescens in mung bean, pointing to their use in plant disease control and growth enhancement.